Industria en el "país abanico". Leyes de promoción industrial de Jujuy en la primera mitad del siglo XX - Soledad Bernasconi, Mariana (Universidad de San Buenaventura - Cali, 2017)
From the side effectsof the First World War a group of politicians and intelectuals began to make an inventory of the spare parts that the Argentine agro-export growth had been leaving. The promotion laws that Jujuy enacted from the 1920s can be considered part of the proposals and alternatives to boost Argentine economic development. Therefore, the main objective of this study was to analyze them to determine these rules impact on the local industrial sector performance during the period. These initiatives did not have the expected effects because can not to attribute positive results.